Linking Flood and Flood Resilience Through Scientometric Review for Future Research - Anthony, Peter; Abdul Majid, Roshida; Tukiman, Nor Izura (International Journal of Environment, Architecture, and Societies, 2023)
Flood resilience architecture is riddled with challenging and complicated issues. Few studies, meanwhile, have attempted to map the global research on this crucial area. The objectives of the study are connections among the stakeholders, the main areas of research, and the available direction in the body of knowledge. 635 document-related bibliographic records that were collected from Scopus were systematically and quantitatively analysed using the scientific mapping method. The findings showed that the top 3 keywords most frequently used in the field were floods, flood control, and flooding. The top 3 least discussed topics/issues were decision-making, rain, and urban resilience. This study's main contribution and distinction come from its status as the first to present an inclusive, comprehensive, and overall overview of the examined literature. By identifying key research topics, journals, institutions, and countries, as well as how these are connected within currently accessible studies on the sector, this study adds value to the existing literature. The findings highlight the limitations in the existing research and offer directions for future study, where they suggested that as a way of resilience to the problems, future study potential lies in the least studied topics. For the world of practice, the study provides a convenient point of reference for practitioners, decision-makers, and new researchers in the field. Therefore, this study increases the level of awareness of flood and flood resiliency in the housing sector.